PENGELOLAAN APLIKASI PLATFORM RUANG GURU DAN TENAGA KEPENDIDIKAN DI SDN PERCOBAAN PALANGKA RAYA - Munawarah, Rizka Nabila; Dakir, Dakir; Irawan, Rio (Universitas Tanjungpura, 2025)
This study aims to analyze the management of the Ruang Guru and GTK (Teachers and Education Personnel) applications at SD Negeri Percobaan Palangka Raya in supporting teaching and school administration at the elementary level. The background of this research is based on the demand for educational digitalization in the Industrial Revolution 4.0 era and the freedom to learn policy, which encourages schools to integrate technology into learning processes and school management. This research employed a qualitative descriptive approach with data collection techniques consisting of in-depth interviews, observation, and documentation. The research informants were the principal, teachers, and education personnel selected through purposive sampling. Data were analyzed using an interactive analysis model including data reduction, data presentation, and conclusion drawing, and validated by source and method triangulation. The findings show that the implementation of the Ruang Guru application assists teachers in preparing lesson plans, expanding access to online training, and enriching teaching methods, while the GTK application contributes to more efficient administration, reporting, and professional development of education staff. Nevertheless, several challenges remain, such as limited internet infrastructure, inadequate devices, and low digital literacy among senior teachers. The school addressed these challenges through internal training, technical assistance, and scheduling the use of applications alternately. This study concludes that the management of the Ruang Guru and GTK applications in elementary schools has the potential to improve the quality of learning and the effectiveness of administration, provided that leadership support, teacher collaboration, and policy commitment to strengthening digital infrastructure are ensured.